Nursing Care of Spontaneous Ventilation Disorder in Mr. D With Post-Thoracostomy Decortication on the Indication of Right Hydropneumothorax in the Intensive Care Unit (ICU) Room of RSUD Prof. Dr. Margono Soekarjo Purwokerto - Wahidah, Silvi Nuraeni; Siwi, Adiratna Sekar (Faculty of Medicine, Universitas Tadulako, 2025)
Hydropneumothorax is a medical emergency, a condition in which the presence of air and fluid in the pleural cavity results in the collapse of lung tissue. The prevalence of hydropneumothorax has not been recorded, but ranges from 2.4-17.8 per 100,000 population each year. This case study aims to describe the nursing care of spontaneous ventilation disorders in Mr. D with post-thoracostomy decorticization of indications of hydropneumothorax dextra in the Intensive Care Unit (ICU) Room of Prof. Dr. Margono Soekarjo Purwokerto Hospital. The research method is a descriptive case study. Data collection techniques, including: interviews, physical examinations, observations, documentation studies. Patients with a nursing diagnosis of spontaneous ventilation disorders are given a semi-fowler position. It was concluded that the case of hydropneumothorax dextra, post thoracostomy was a problem with airway obstruction. This leads to weakening of the respiratory muscles and impaired spontaneous ventilation. The action given, namely the provision of a semi-fowler position, effectively helps reduce shortness of breath, increases respiratory rate. After nursing care was carried out, spontaneous ventilation disorders in Mr. D with post-thoracostomy decortication of indications of hydropneumothorax dextra in the Intensive Care Unit (ICU) Room of Prof. Dr. Margono Soekarjo Hospital Purwokerto have not been resolved.